1998
DOI: 10.1016/s1078-5884(98)80109-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interobserver variability in ultrasound measurements of abdominal aortic diameter. The Tromsø study

Abstract: Ultrasound measurements of the maximal diameter can be obtained with a high degree of accuracy. Inexperienced sonographers may achieve acceptable performance given appropriate training and surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 15 publications
2
86
0
2
Order By: Relevance
“…14 A study by Singh et al 56 assessed the variability of ultrasonographic measurements at different levels of the abdominal aorta and concluded inexperienced sonographers might achieve acceptable performance given appropriate training and surveillance. All of the studies in this review reported limited experience with minimal training of the ED providers performing the bedside US, with favorable outcomes as well.…”
Section: Discussionmentioning
confidence: 99%
“…14 A study by Singh et al 56 assessed the variability of ultrasonographic measurements at different levels of the abdominal aorta and concluded inexperienced sonographers might achieve acceptable performance given appropriate training and surveillance. All of the studies in this review reported limited experience with minimal training of the ED providers performing the bedside US, with favorable outcomes as well.…”
Section: Discussionmentioning
confidence: 99%
“…6,41,42 Singh et al assessed the variability of sonographic measurements at different levels of the abdominal aorta and concluded that inexperienced sonographers might achieve acceptable performance with appropriate training and surveillance. 43 Nguyen et al also further confirmed that novices could be trained to screen after 15 days. In the setting of technically difficult cases, continued quality improvement with scan experience was essential.…”
Section: Level Of Experiencementioning
confidence: 87%
“…However, there is a relatively higher rate of interobserver and intraobserver variability with ultrasonography than with angiotomography, 18 but this variability is no larger than 4 mm, on average. 19 Additionally, ultrasonography is also able to provide a better approximation to the true perpendicular diameter of an abdominal aortic aneurysm, since it is not affected by the angle of the aorta, which impacts on tomography results at angles greater than 25°. 20 Endoleaks can be detected by ultrasound using color spectral analysis to show blood flow.…”
Section: Discussionmentioning
confidence: 99%